О вибрационном воздействии лунно-солнечных приливов на геодинамические процессы - Довбнич, М.М.; Солдатенко, В.П. (Видавничий дім "Академперіодика" НАН України, 2008)
On the basis of the complex analysis of seismic events in the Crimea and the results of modeling a tide-induced stress-strain state of the tectonosphere, the conclusion about an essential influence of the tidal vibrating as a triggering mechanism of earthquakes is made.